LOCALIZATION OF NEOLOGISMS IN THE UZBEK LANGUAGE - ADOPTION AND NATIONAL CHARACTERISTICS OF NEOLOGISMS IN THE TECHNOLOGICAL FIELD - Ergashev Tulkinjon Tukhtamurodovich (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article analyzes the formation, mutual influence, and lexicographic interpretation of neologisms in English and Uzbek languages through synchronic and diachronic approaches. It examines the borrowing of English words into Uzbek (e.g., "selfi," "trend," "influencer") under the influence of globalization and socio-cultural changes, as well as their localization processes. The principles of incorporating neologisms into English dictionaries (e.g., OALD, Cambridge Dictionary) and Uzbek sources like the Explanatory Dictionary of the Uzbek Language are also explored. The article investigates the semantic and contextual evolution of modern concepts such as project-based learning, linguocultural studies, hybrid learning, cloud computing, AI, and cancel culture. It concludes with recommendations for enhancing the interpretation of neologisms through bilingual dictionaries and the development of online lexicographic resources. The study is of significant value for researchers in linguistics, lexicography, and intercultural communication.